2017
DOI: 10.1021/acs.biochem.7b00769
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evidence for the Dopamine-First Mechanism of Norcoclaurine Synthase

Abstract: Norcoclaurine synthase (NCS) is a Pictet-Spenglerase that catalyzes the first key step in plant benzylisoquinoline alkaloid metabolism, a compound family that includes bioactive natural products such as morphine. The enzyme has also shown great potential as a biocatalyst for the formation of chiral isoquinolines. Here we present new high-resolution X-ray crystallography data describing Thalictrum flavum NCS bound to a mechanism-inspired ligand. The structure supports two key features of the NCS “dopamine-first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 24 publications
0
73
0
Order By: Relevance
“…Attempts at expressing native sequences of the STRs (Table S1 in the Supporting Information) using various expression plasmids as well as various E. coli hosts, chaperones, and expression conditions resulted in no visible overexpression bands detectable by SDS PAGE, although the enzyme preparations allowed us to run the transformation of the natural substrate to completion within 24 hours at 1–2 m m substrate concentration 6b. Interestingly, highest activities were found when the STRs were expressed with an N‐terminal His 6 ‐tag.…”
mentioning
confidence: 99%
“…Attempts at expressing native sequences of the STRs (Table S1 in the Supporting Information) using various expression plasmids as well as various E. coli hosts, chaperones, and expression conditions resulted in no visible overexpression bands detectable by SDS PAGE, although the enzyme preparations allowed us to run the transformation of the natural substrate to completion within 24 hours at 1–2 m m substrate concentration 6b. Interestingly, highest activities were found when the STRs were expressed with an N‐terminal His 6 ‐tag.…”
mentioning
confidence: 99%
“…Furthermore, the dual role of Tyr108, contributing to the electrostatic properties of the active site, but also in defining the shape of the cavity entrance was established . Most recently, the studies by Lichman et al . presented new high‐resolution X‐ray crystallography data describing NCS‐ Tf bound to a mechanism‐inspired ligand, which supported the key features of ‘the dopamine‐first mechanism’.…”
Section: Pictet‐spenglerasesmentioning
confidence: 94%
“…The first crystallographic structure of NCS from T. flavum in its complex with dopamine and the non-reactive substrate analogue 4-hydroxybenzaldehyde was obtained by our research group [ 70 ] allowing to understand NCS catalytic mechanism and kinetics [ 71 ]. Afterwards, it was demonstrated that a dopamine first mechanism governs the stereoselective production of ( S )-norcoclaurine [ 72 , 73 ] and showed also that the kinetic behavior can explain the ineffectiveness of recombinant NCS in vivo systems. Nevertheless, NCS is a powerful tool for the in vitro asymmetric synthesis of ( S )-norcolaurine and derivatives.…”
Section: Norcolaurine Synthase: the Gate Of Bia Chiralitymentioning
confidence: 99%